PCz/BaO nanocomposites: Synthesis, characterization, and energy storage properties - Beyazay, Emre; Karabul, Yasar; Kilic, Mehmet; Korkut, Sibel Eken; Ozdemir, Zeynep Guven (ELSEVIER, 2022)
This study focuses on both synthesis and structural characterization of polycarbazole/barium oxide (PCz/BaO) nanocomposites and the determination of their frequency-based electrical properties such as complex permit-tivity, tangent loss, and alternating current (ac) conductivity. While PCz was synthesized by using carbazole monomers, BaO nanoparticles (NPs) were obtained by using the co-precipitation method. PCz matrix and BaO NPs were examined by scanning and transmission electron microscopes, X-ray diffraction, and Fourier Trans -formed Infrared Spectroscopy methods. The electrical properties of the PCz/BaO nanocomposites showed that the energy storage ability of the PCz can be improved with the addition of BaO NPs up to 10 wt% at the low frequencies. Furthermore, the 2.5 wt% BaO NPs contribution causes an increase in epsilon' and a decrease in epsilon of PCz. Additionally, it has been determined that BaO NPs doping significantly increases the ac conductivity of the PCz matrix in the low-and mid-frequency regions.
Keywords: Conducting polymers; Dielectric propeties; Nanocomposites; ELECTRICAL-CONDUCTIVITY; CONJUGATED POLYMER; Physics